2016
DOI: 10.1038/srep32217
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Electrochemical Hydrogen Evolution Reaction at Insulating Boron Nitride Nanosheet on Inert Gold Substrate

Abstract: It is demonstrated that electrochemical hydrogen evolution reaction (HER) proceeds very efficiently at Au electrode, an inert substrate for HER, modified with BNNS, an insulator. This combination has been reported to be an efficient electrocatalyst for oxygen reduction reaction. Higher efficiency is achieved by using the size controlled BNNS (<1 μm) for the modification and the highest efficiency is achieved at Au electrode modified with the smallest BNNS (0.1–0.22 μm) used in this study where overpotentials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 28 publications
1
53
0
1
Order By: Relevance
“…Therefore, a metal substrate or defects in h-BN can promote or affect catalytic reactions on the h-BN surface [38]. This theoretical suggestion has been proved experimentally where it has been demonstrated that Au electrodes modified with boron nitride nanosheet (BNNS) in the acid media indeed can act as effective electrocatalysts not only for ORR [47,48], but also for the hydrogen evolution reaction (HER) [49]. It has been demonstrated that overpotential for ORR at gold electrode is reduced by 0.27 V by the modification with BNNS, although it is still high compared with Pt electrode and oxygen is mainly reduced to H 2 O 2 via 2electron process [47,48].…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, a metal substrate or defects in h-BN can promote or affect catalytic reactions on the h-BN surface [38]. This theoretical suggestion has been proved experimentally where it has been demonstrated that Au electrodes modified with boron nitride nanosheet (BNNS) in the acid media indeed can act as effective electrocatalysts not only for ORR [47,48], but also for the hydrogen evolution reaction (HER) [49]. It has been demonstrated that overpotential for ORR at gold electrode is reduced by 0.27 V by the modification with BNNS, although it is still high compared with Pt electrode and oxygen is mainly reduced to H 2 O 2 via 2electron process [47,48].…”
Section: Introductionmentioning
confidence: 94%
“…7 Although it is intrinsically insulating (i.e., band gap of 3.6 to 7.1 eV), 8 hexagonal boron nitride (h-BN) has attracted considerable attention in oxygen reduction reaction (ORR) 9,10 and hydrogen evolution reaction (HER) catalysis. 11 This is because the band gap of monolayer h-BN can be considerably reduced by introducing defects such as B/N vacancies and impurities, 12 and tuned to an extent through decoration with hydrogen atoms. 13 Moreover, as electron tunneling through ultrathin h-BN layers is possible, 14 electronic interaction with the underlying metal support substrate (i.e., through mixing of the d z 2 metal orbitals with the N-p z and B-p z orbitals of h-BN) can tune electrochemical (electrocatalytic) activity.…”
mentioning
confidence: 99%
“…For an ideal electrocatalyst, it has to be in thermoneutral, that is, Δ G H ∼0 eV – meaning adsorption and desorption (of H 2 ) energy should be optimum . The reported theoretical frameworks for 2D materials modified metals mostly hold in an acidic medium where either adsorption/desorption energy optimization or Fermi level modification are proposed as the basic mechanism aiding for higher activities . Subbaraman et al proposed a different mechanism for improved electrocatalysis of electrodeposited 3d‐metal oxyhydroxides on a gold electrode in alkaline medium .…”
mentioning
confidence: 99%